2012
DOI: 10.1620/tjem.226.19
|View full text |Cite
|
Sign up to set email alerts
|

Association between Increased Serum Osteoprotegerin Levels and Improvement in Bone Mineral Density after Parathyroidectomy in Hemodialysis Patients

Abstract: Secondary hyperparathyroidism (SHPT) is a common complication in chronic renal disease. Osteoprotegerin (OPG), an extracellular cytokine receptor secreted by osteoblasts, can promote bone formation by inhibiting the function of osteoclasts. Hemodialysis (HD) patients have elevated serum OPG levels. OPG secretion can be suppressed with high parathyroid hormone (PTH) levels. HD patients with refractory SHPT can benefit from parathyroidectomy (PTX) treatment, but the changes of serum OPG, bone turnover markers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
(48 reference statements)
3
9
0
Order By: Relevance
“…The preoperatively elevated OPG level of 10.9 ± 1 pmol/L in our study is in concordance with the findings reported by Zheng et al [47], who also observed elevated preoperative OPG levels in patients with sHPT. They observed increasing OPG levels within 2 weeks after PTX and explained this effect with the loss of the inhibiting effect of PTH [47].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The preoperatively elevated OPG level of 10.9 ± 1 pmol/L in our study is in concordance with the findings reported by Zheng et al [47], who also observed elevated preoperative OPG levels in patients with sHPT. They observed increasing OPG levels within 2 weeks after PTX and explained this effect with the loss of the inhibiting effect of PTH [47].…”
Section: Discussionsupporting
confidence: 93%
“…They observed increasing OPG levels within 2 weeks after PTX and explained this effect with the loss of the inhibiting effect of PTH [47]. However, we observed no significant change perioperatively.…”
Section: Discussionsupporting
confidence: 41%
“…The pathophysiology of the “hungry bone syndrome” observed after PTX is similar to the bone marrow ablation model used to investigate osteogenic capacity [10, 11]. Accordingly, PTX induces an initial rapid and prominent activation of bone synthetic activity, followed by a suppression of osteoclast activity which persists for at least one year [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Continuously elevated PTH causes bone resorption and net bone loss . This is counteracted by a large increase in circulating osteoprotegerin which decreases osteoclast activation . The sudden drop in PTH after surgery leaves osteoprotegerin unopposed, inhibiting osteoclast activation and reducing bone resorption resulting in hypocalcaemia.…”
Section: Discussionmentioning
confidence: 99%
“…11 This is counteracted by a large increase in circulating osteoprotegerin which decreases osteoclast activation. 14 The sudden drop in PTH after surgery leaves osteoprotegerin unopposed, inhibiting osteoclast activation and reducing bone resorption resulting in hypocalcaemia. The significant difference in PTH between the groups may also reflect delays in parathyroidectomy and more severe hyperparathyroidism at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%